Top quark anomalous couplings at the high-luminosity phase of the LHC - Deliot, F. (2019)
The combination of the latest and most precise measurements of several top quark properties is presented in this paper in order to establish allowed regions on anomalous contributions to the Lorentz structure of the Wtb vertex. These measurements include single top production cross-sections, W boson helicity fractions and forward–backward asymmetries, both at Tevatron and at the Large Hadron Collider (LHC), up to a center-of-mass energy of 13 TeV. The results obtained at 95% Confidence Level (CL) for the top quark anomalous couplings are compared with the limits extracted from a combination that includes the expected measurements at the future High-Luminosity run of the LHC.